The relevance of BDNF for neuroprotection and neuroplasticity in multiple sclerosis - Maiworm, Michelle (Frontiers in Neurology, 2024)
Background Neuroplasticity as a mechanism to overcome central nervous system injury resulting from different neurological diseases has gained increasing attention in recent years. However, deficiency of these repair mechanisms leads to the accumulation of neuronal damage and therefore long-term disability. To date, the mechanisms by which remyelination occurs and why the extent of remyelination differs interindividually between multiple sclerosis patients regardless of the disease course are unclear. A member of the neurotrophins family, the brain-derived neurotrophic factor (BDNF) has received particular attention in this context as it is thought to play a central role in remyelination and thus neuroplasticity, neuroprotection, and memory. Objective To analyse the current literature regarding BDNF in different areas of multiple sclerosis and to provide an overview of the current state of knowledge in this field. Conclusion To date, studies assessing the role of BDNF in patients with multiple sclerosis remain inconclusive. However, there is emerging evidence for a beneficial effect of BDNF in multiple sclerosis, as studies reporting positive effects on clinical as well as MRI characteristics outweighed studies assuming detrimental effects of BDNF. Furthermore, studies regarding the Val66Met polymorphism have not conclusively determined whether this is a protective or harmful factor in multiple sclerosis, but again most studies hypothesized a protective effect through modulation of BDNF secretion and anti-inflammatory effects with different effects in healthy controls and patients with multiple sclerosis, possibly due to the pro-inflammatory milieu in patients with multiple sclerosis. Further studies with larger cohorts and longitudinal follow-ups are needed to improve our understanding of the effects of BDNF in the central nervous system, especially in the context of multiple sclerosis.